2021
DOI: 10.38045/ohrm.2022.3.01
|View full text |Cite
|
Sign up to set email alerts
|

The role of boron in prevention of osteoarticular diseases and its distribution in the Republic of Moldova

Abstract: Introduction. Boron is a trace mineral that is supposed to be essential for human health. Organic plant based boron compounds are highly bioavailable for humans and can positively influence minerals such as calcium, phosphorus, magnesium and act in synergy with vitamin D, which are beneficial for osteoarticular health. Material and methods. We made an analysis of 126 bibliographic sources and mapped the Republic of Moldova to the content of boron in deep water and to the adults’ prevalence of rheumatoid arthr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…The present study showed that SPP and BA could enhance nutrient digestibility and intestinal glucose and fatty acid transporters, as well as regulate hepatic lipogenesis. B is absorbed from the gastrointestinal tract and is rapidly distributed into tissues [ 27 , 28 ]. This rapid action of B probably increased serum B levels with SPP and BA supplementation in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The present study showed that SPP and BA could enhance nutrient digestibility and intestinal glucose and fatty acid transporters, as well as regulate hepatic lipogenesis. B is absorbed from the gastrointestinal tract and is rapidly distributed into tissues [ 27 , 28 ]. This rapid action of B probably increased serum B levels with SPP and BA supplementation in this study.…”
Section: Discussionmentioning
confidence: 99%